IMPLEMENTASI LITERASI DIGITAL DI SD NEGERI 81 PALEMBANG DALAM PEMBELAJARAN ABAD 21 - Rahmah Zabita Diani; Sighatiah Andayani; Monika Monika; Elen Priana; Esy Salsya Ariska (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study aims to describe the implementation of digital literacy at Public Elementary School 81 Palembang within the framework of 21st-century learning. The main issue addressed in this research concerns the need for mastering digital literacy as a fundamental competency that enables students to compete in an era of rapidly advancing information technology. The scope of the study includes educational institution policies, supporting facilities, teachers’ competencies, students’ responses and capabilities, as well as challenges encountered during the implementation of digital literacy. The research employs a qualitative approach using in-depth interviews and direct observations as data-collection techniques. The findings indicate that Public Elementary School 81 Palembang demonstrates a strong commitment to integrating digital technology into the learning process through supportive policies and the provision of facilities such as Chromebooks and adequate internet access. Teachers show sufficient competence in using digital learning technologies, while students display enthusiasm and benefit from learning through electronic media. The main challenges include variations in digital literacy levels among teachers and students, limited time for guidance, and the need for stronger parental support. Strengthening strategies implemented by the school include professional development programs for teachers, the establishment of an Information and Communication Technology (ICT) team, and active engagement with parents. Overall, the study concludes that the implementation of digital literacy contributes significantly and positively to improving the quality of 21st-century learning at Public Elementary School 81 Palembang, although continuous efforts are still required to address existing challenges. ABSTRAK Kajian ini dimaksudkan untuk menggambarkan penerapan literasi digital di Sekolah Dasar Negeri 81 Palembang dalam kerangka pembelajaran era ke-21. Dasar permasalahan melibatkan perlunya penguasaan literasi digital sebagai kompetensi fundamental bagi peserta didik untuk dapat berkompetisi di era informasi teknologi yang maju dengan cepat. Ruang lingkup kajian mencakup kebijakan institusi pendidikan, sarana penunjang, kemampuan tenaga pengajar, tanggapan serta kapabilitas siswa, dan hambatan yang ditemui dalam implementasi literasi digital. Pendekatan penelitian mengadopsi metode kualitatif melalui teknik pengumpulan data berupa wawancara mendalam dan pengamatan langsung. Temuan kajian mengindikasikan bahwa Sekolah Dasar Negeri 81 Palembang menunjukkan komitmen tinggi melalui kebijakan yang memfasilitasi integrasi teknologi digital dalam proses pembelajaran, yang didukung oleh sarana seperti Chromebook dan koneksi internet yang cukup. Para pendidik menunjukkan kompetensi memadai dalam penggunaan teknologi pembelajaran digital, sedangkan peserta didik menunjukkan antusiasme dan mendapatkan manfaat dalam pembelajaran melalui media elektronik. Tantangan utama meliputi variasi tingkat literasi digital di antara guru dan siswa, keterbatasan waktu bimbingan, serta dukungan dari orang tua yang masih memerlukan peningkatan. Strategi penguatan yang diimplementasikan mencakup program pelatihan bagi tenaga pengajar, pembentukan tim Teknologi Informasi dan Komunikasi sekolah, serta interaksi aktif dengan pihak orang tua. Kajian ini menyimpulkan bahwa penerapan literasi digital memberikan kontribusi positif yang substansial dalam meningkatkan mutu proses pembelajaran era ke-21 di Sekolah Dasar Negeri 81 Palembang, meskipun tetap diperlukan upaya berkelanjutan untuk menangani hambatan yang ada.